Earthquake Preparedness Knowledge and Practice of Secondary Level - Mandal, Punam Kumari; Khadgi, Dipika; Lage, Shrijana; Yangden, Namita; Subedi, Sabitra (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
This paper attempts to analyze earthquake preparedness knowledge and practice of secondary-level students in Nepal. In this paper, earthquake preparedness knowledge and practice refer to the understanding and implementation of measures to minimize the potential damage and loss of life caused by earthquakes, including proper building design and construction, emergency planning, and regular drills and training for individuals and communities. Earthquake preparedness knowledge and practice are essential for secondary-level school students because the losses of mortalities, morbidities, and economics from earthquakes cannot be predicted in the world. In this paper, a descriptive research design and quantitative approach as well as primary sources of data were used. Primary data were collected from semi-structured questionnaires with the students of Grades 9 and 10 of the government school of Bhaktapur, Bagmati Province. Of the total 96 students were censused using the rule of thumb method. The findings show that about 91.7% reported they heard the earthquake preparedness, 16.9% prepared with a Go bag, and 2.1% practiced duck, cover, and hold methods during the shock of the earthquake. The result reveals that about 50 percent of the total students have adequate knowledge of earthquake preparedness while they have limited practice. It can conclude that adequate preparedness practices were needed for secondary-level students. In addition, they should be aware of and understand the causes, nature, and effects of natural hazards skills to enable proactive prevention and mitigation of disasters.